2012
DOI: 10.1542/peds.2011-2411
|View full text |Cite
|
Sign up to set email alerts
|

Parental Psychological Well-Being and Behavioral Outcome of Very Low Birth Weight Infants at 3 Years

Abstract: Parents report more behavioral and emotional problems in VLBW children at age 3 if they themselves have had symptoms of depression, parenting stress, or weak sense of coherence 1 year earlier. The new finding of this study was to show the significance of the father's psychological well-being on the behavioral development of a preterm child.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
78
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(81 citation statements)
references
References 50 publications
3
78
0
Order By: Relevance
“…16 Some studies of preschool children born preterm have used the well-known instrument the Child Behavior Checklist (CBCL), 17,18 which defines domains of dysfunction, and have reported increased CBCL Total Problem scores and Internalizing and Externalizing scores, but none of the studies has reported on the CBCL-Dysregulation Profile (CBCL-DP). 1921 The CBCL-DP has been defined as representing a syndrome not defined by the DSM and is related to severe psychopathology and outcomes 22 in youth.…”
Section: Introductionmentioning
confidence: 99%
“…16 Some studies of preschool children born preterm have used the well-known instrument the Child Behavior Checklist (CBCL), 17,18 which defines domains of dysfunction, and have reported increased CBCL Total Problem scores and Internalizing and Externalizing scores, but none of the studies has reported on the CBCL-Dysregulation Profile (CBCL-DP). 1921 The CBCL-DP has been defined as representing a syndrome not defined by the DSM and is related to severe psychopathology and outcomes 22 in youth.…”
Section: Introductionmentioning
confidence: 99%
“…A possible contributing factor to positive behavioural outcomes may be due to an increased interaction between parents and their children in both groups during the study period and perhaps this was reinforced by the regular email communication with parents. A similar outcome was found by Huhtala et al, who reported that their cohort of very low birth weight children at three years of age did not have more behavioural problems than their full-term peers (Huhtala et al, 2012).…”
Section: Discussionsupporting
confidence: 84%
“…16,17 Preterm infants' behavioral, emotional, and neurologic problems at later ages have been shown to be multietiologic and explained in part by neurologic and cognitive deficits due to prematurity 1,2,[18][19][20][21] and psychosocial factors. [22][23][24] The role of the preterm infant' s regulatory competence in the development of later behavioral symptoms is still unknown. Persistent crying problems that last beyond 3 months of age have been related to later hyperactivity and other behavioral problems in the full-term population.…”
mentioning
confidence: 99%